2017
DOI: 10.1002/cctc.201601228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Functionalization of the Ordered Mesoporous Carbon Support Surface on Iron Catalysts for the Fischer–Tropsch Synthesis of Lower Olefins

Abstract: Ordered mesoporous carbon (CMK‐3) with different surface modifications is applied as a support for Fe‐based catalysts in the Fischer–Tropsch to olefins synthesis (FTO) with and without sodium and sulfur promoters. Different concentrations of functional groups do not affect the size (3–5 nm) of Fe particles in the fresh catalysts but iron (carbide) supported on N‐enriched CMK‐3 and a support with a lower concentration of functional groups show higher catalytic activity under industrially relevant FTO conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 43 publications
3
47
0
Order By: Relevance
“…Owing to conversion of the Fe-NPs into the active carbidep hase, core-shell particles had formed and were observed in all catalysts, albeit mostly in the promoted ones. [34] Finally,t hese findings indicate that attaching colloidalp articles to an oxidized carbon nanotube support resulted in deactivation during the catalytic reactiono wing to the poor interaction of the Fe-NPs with the surface. This nicely matched the Mçssbauer spectroscopy results (Tables S2 and Figure S3) that the same amount of Fe-NPs was converted into the e-Fe 2.2 Ca nd c-Fe 5 C 2 phases, which are considered activei n FTO.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Owing to conversion of the Fe-NPs into the active carbidep hase, core-shell particles had formed and were observed in all catalysts, albeit mostly in the promoted ones. [34] Finally,t hese findings indicate that attaching colloidalp articles to an oxidized carbon nanotube support resulted in deactivation during the catalytic reactiono wing to the poor interaction of the Fe-NPs with the surface. This nicely matched the Mçssbauer spectroscopy results (Tables S2 and Figure S3) that the same amount of Fe-NPs was converted into the e-Fe 2.2 Ca nd c-Fe 5 C 2 phases, which are considered activei n FTO.…”
mentioning
confidence: 94%
“…[21][22][23] Nevertheless, there are many porous carbon materials that can be used as catalysts upports such as activated carbon and graphitic and templated carbon. [30][31][32][33][34] The attachment of colloidal particles to support materials has so far not been researched abundantly;h owever,i th as been found that the support material can alter the behavior of the particlesd uring catalysis. [27][28][29] More importantly,i tw as found that functionalization of carbon supports suppressed particleg rowth by the anchoring particles, thereby increasing the stability of the impregnated catalysts.…”
mentioning
confidence: 99%
“…The requirements carbons have to meet are strongly dependent on their applications. As electrode materials they have to provide high conductivities and high specific surface areas [7], as support materials in catalysis they have to ensure strong interaction between the surface and the active species [8], and in adsorptive applications such as wastewater purification they have to remove chemicals like heavy metal ions [9] or pharmaceuticals [10] rapidly and to a large extent. Therefore, the porosity and the surface polarity of carbons are key and need to be specifically tailored to the corresponding application.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,12 Furthermore, carbonaceous supports stand out due to high chemical stability, high surface area, variable pore structure, and versatile surface chemistry. [13][14][15] The most widely applied method for the preparation of carbon-supported FTO catalysts is deposition of the iron precursor (most often by solution impregnation) on the surface of a pre-formed carbon material (e.g., carbon nanotubes, porous carbons, or carbon nanofibers) followed by drying and calcination. 7,9,12,14 However, this process can suffer from its non-continuous character and potentially inhomogeneous distribution of the active phase after drying and calcination.…”
Section: -10mentioning
confidence: 99%
“…[13][14][15] The most widely applied method for the preparation of carbon-supported FTO catalysts is deposition of the iron precursor (most often by solution impregnation) on the surface of a pre-formed carbon material (e.g., carbon nanotubes, porous carbons, or carbon nanofibers) followed by drying and calcination. 7,9,12,14 However, this process can suffer from its non-continuous character and potentially inhomogeneous distribution of the active phase after drying and calcination. One-pot synthesis of iron/carbon catalysts by pyrolyzing mixtures of precursors of support and metal is one option to overcome this drawback.…”
Section: -10mentioning
confidence: 99%